Students’ Activity Involvement for Speaking Ability Improvement - Fitrotul Mufaridah (ELLITE, 2017)
To make students’ ideas become real, it needs act that can make them bring themselves to explore what is in their mind. The action done by students in the classroom would encourage them to be able to be creative in speaking class. The creativity should be facilitated by the teacher by providing more rooms for the students to involve much in the classroom activities. It is more meaningful for the teacher to design the classroom activities by involving students’ participation. The design should facilitate both teacher and students to practice the teaching and learning activities creatively, so the class would be more interesting and more authentic. The students’ involvement can also empower the student-teacher relationship and bridge them to minimize gap. In the process of having speaking classroom activities, the teacher can learn more on how to listen to students’ ideas and how to appreciate them respectfully to their creativity. The teachers can build the students’ creativity and guide them how to implement it well for students’ learning experience. In another side, the students are invited to explore their smart ideas in developing learning experience which is leading them to do creative and meaningful learning activities. They come to class not only as the passive participants of the learning activities but also as the active participants in proposing and acting their ideas in speaking class. It is really challenging involvement for the students. It brings them to have bigger responsibility in doing learning process. So, the students’ activity involvement are experienced them to enrich their creativity and to enhance their speaking ability.   Keywords: classroom activity design, learning experience, meaningful learning, challenging involvement, creativity enrichment.